A multi-beam optical scanning device. - Aris, Ishak; Koh, Siaw Paw (2008)

(untitled)
The present invention relates to an optical scanning device. The optical scanning device essentially comprises a laser scanner unit having a laser source and a plurality of scanning heads, a scanner head controlling unit; and a scanning platform. The scanning heads are adapted for controlling the path of laser beams. The optical scanning device is adapted to further comprise an artificial intelligent system having an interface for data input and a database for storing genetics algorithm. The artificial intelligent system is adapted for regulating the operation of the scanner head in synchronization in scanning sequences in response to the data inputted and according to the genetic algorithm. The artificial intelligent system regulates the scanning head via the controlling unit and the genetics algorithm is adapted to optimize the scanning speed and implement the optimal scanning sequences. The scanner head controlling unit essentially comprises a plurality of reflector controllers. The scanning heads each comprise a plurality of optical reflectors and a focus lens. The reflectors controllers each is adapted to control the corresponding optical reflector to move such that to regulate the laser beams to the focus lens.